2021
DOI: 10.1002/tox.23338
|View full text |Cite
|
Sign up to set email alerts
|

Modifying effects of menthol against benzo(a)pyrene‐induced forestomach carcinogenesis in female Swiss mice

Abstract: Benzo(a)pyrene (BaP) is a polycyclic aromatic hydrocarbon widespread in the environment and closely associated to tobacco use, which is an important risk factor for highly incident stomach cancer. Menthol, a monoterpene extracted from Mentha genus species, has multiple biological properties, including anti‐inflammatory and gastroprotective properties, but its effects on carcinogenesis are still to be fully understood. Thus, we evaluated the modifying effects of Ment against BaP‐induced forestomach carcinogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…The anti-inflammatory effects of exogenous menthol were also evident on the microscopic level, given that treated animals displayed diminished pathogen-induced colonic epithelial apoptosis (Figure 4C). In support, previous in vivo studies reported potent anti-apoptotic effects upon menthol treatment, given decreases in pro-apoptotic molecules such as cleaved caspase-3 and Bax protein and/or increases in anti-apoptotic molecules including Bcl-2 and HSP-70 [32,33,46,47]. The dampened apoptotic responses upon C. jejuni infection were accompanied by lower numbers of macrophages and monocytes in the colonic mucosa in menthol-pretreated mice on day 6 p.i.…”
Section: Discussionsupporting
confidence: 84%
“…The anti-inflammatory effects of exogenous menthol were also evident on the microscopic level, given that treated animals displayed diminished pathogen-induced colonic epithelial apoptosis (Figure 4C). In support, previous in vivo studies reported potent anti-apoptotic effects upon menthol treatment, given decreases in pro-apoptotic molecules such as cleaved caspase-3 and Bax protein and/or increases in anti-apoptotic molecules including Bcl-2 and HSP-70 [32,33,46,47]. The dampened apoptotic responses upon C. jejuni infection were accompanied by lower numbers of macrophages and monocytes in the colonic mucosa in menthol-pretreated mice on day 6 p.i.…”
Section: Discussionsupporting
confidence: 84%
“…In another study, female Swiss mice were administered benzo(a) pyrene to induce cancer. Treatment with menthol (50 mg/kg of body weight, twice a week) at the initial stage of benzo(a)pyrene administration showed a reduced incidence of precancerous gastric lesions owing to reduced genotoxicity, reduced cell proliferation, and regulated apoptosis (Santo et al, 2021).…”
Section: Inhibition Of Tumor Proliferationmentioning
confidence: 99%
“…Particularly, in vitro experiments have revealed the anti-proliferative potential of menthol against various tumor cell lines (Fatima et al, 2021). Mechanistically, menthol induces apoptosis in cancer cells, indicating its role as an anticancer agent (Beck et al, 2007) against a variety of cancers, such as prostate cancer (Kim et al, 2009), colon cancer (Faridi et al, 2016), skin cancer (Fatima et al, 2021), uveal melanoma (Walcher et al, 2018), pancreatic ductal Frontiers in Pharmacology frontiersin.org adenocarcinoma (Cucu et al, 2014), gastric cancer (Santo et al, 2021), liver cancer (Lin et al, 2001), leukemia (Lu et al, 2007a), and bladder cancer (Li et al, 2009) (Figure 2). Irrespective of these data, the anticancer properties of menthol have not been sufficiently implemented in clinical practice.…”
mentioning
confidence: 99%